ANALISIS KESALAHAN MENULIS MATEMATIS SISWA PADA MATERI PERSAMAAN LINEAR DUA VARIABEL - Rio Febrianto Arifendi; Ainun Indah Mustika Eden; Muhammad Yusi Kamhar; Waskitorini Waskitorini (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to analyze the mathematical writing errors of students in solving linear equations of two variables at SMP Negeri 5 Wolowaru. Using a qualitative descriptive approach with instruments in the form of description tests and interviews. The results of the study showed that from 23 students of class VIII A SMP Negeri 5 Wolowaru common mistakes that often occurred included: (1) errors at the stage of understanding the problem, where students were accustomed to writing discussions without being known and asked, because generally students were too rushed and did not understand question; (2) errors in the transformation stage, namely students will not write down mathematical models if they are not in the questions, as well as the use of formulas that are still wrong in solving problems; (3) errors in the process ability stage, where the problem solving procedures used by students still do not use the right arithmetic operations; (4) errors at the stage of writing the final answer, which is indicated by the absence of the final result and the conclusion of the answer.